Alcohol dependence and very high risk level of alcohol consumption: a life‐threatening and debilitating disease. (17th July 2018) - Rehm, Jürgen; Guiraud, Julien; Poulnais, Roch; Shield, Kevin D.
Abstract: Women and men with alcohol dependence and very high risk drinking level (VHRDL; defined as drinking >60 or 100 g of ethanol per day, respectively) experience severe health consequences; however, data on the number of these individuals and their health risks are limited. This study estimated (1) the prevalence of VHRDL in 13 European Union (EU) countries among people 15–65 years of age, (2) the risk of disease and injury occurrence associated with VHRDL, (3) the proportion of deaths in nine EU countries attributable to VHRDL and (4) the life expectancy of people in France with VHRDL. Prevalence estimates of VHRDL were based on data obtained from clinical trials and the Global Information System on Alcohol and Health. The risk of disease and injury occurrence was estimated using microsimulations. Population‐attributable fractions (PAFs) were estimated using a Levin‐based methodology. The estimated prevalence of VHRDL in the 13 EU countries examined was 0.74–0.85 percent, with a disease and injury occurrence risk of 13.5 per 100 people with VHRDL per year. For the nine EU countries examined, VHRDL caused 53.6 percent of all liver cirrhosis, 43.8 percent of all pancreatitis and 41.1 percent of oral cavity and pharyngeal cancers (all other PAFs were below 30 percent). Applying these PAFs to French mortality data resulted in a life expectancy of 47–61 years for people with VHRDL—21–35 years less than the general population. These results indicate that the health burdens of VHRDL are potentially large, and interventions targeting VHRDL should be considered when formulating public health policies. Abstract : For the nine EU countries examined, very high risk drinking levels caused 54 percent of all liver cirrhosis, 44 percent of all pancreatitis and 41 percent of oral cavity and pharyngeal cancers